2016
DOI: 10.1186/s41100-016-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Which clinical conditions are most suitable for induction of automated peritoneal dialysis?

Abstract: This review article is an invited review by both the Japanese Society for Dialysis Therapy (JSDT) and Japanese Society for Peritoneal Dialysis (JSPD). Automated peritoneal dialysis (APD) using a cycler machine is an alternative choice for patients who are on peritoneal dialysis (PD) for the treatment of end-stage renal disease (ESRD). The main purpose is to allow more free time and an improved quality of life for PD patients versus continuous ambulatory PD (CAPD). However, it remains unclear which modality is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
(87 reference statements)
2
6
0
Order By: Relevance
“…The great time requirements of manual CAPD exchanges and additional abdominal weight due to dwelling dialysate in between the CAPD exchanges may be more likely to cause discomfort and more interruptions to daily activities, hence impacting HRQOL. In contrast, APD being an overnight procedure entails no dialysate weight bearing and allows more flexibility during the day for patients to pursue work, family and daily activities [ 23 ], which would be associated with better HRQOL. Also, compared to the manual exchanges in CAPD, the use of a dialysis machine in APD may lead to increased compliance with the prescribed PD regime and hence better disease management, which may in turn contribute to higher physical HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…The great time requirements of manual CAPD exchanges and additional abdominal weight due to dwelling dialysate in between the CAPD exchanges may be more likely to cause discomfort and more interruptions to daily activities, hence impacting HRQOL. In contrast, APD being an overnight procedure entails no dialysate weight bearing and allows more flexibility during the day for patients to pursue work, family and daily activities [ 23 ], which would be associated with better HRQOL. Also, compared to the manual exchanges in CAPD, the use of a dialysis machine in APD may lead to increased compliance with the prescribed PD regime and hence better disease management, which may in turn contribute to higher physical HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that depression and cognitive impairment are independent risk factors for mortality in End-Stage Renal Disease (ESRD) patients ( 36 ) and quality of life has been recognized as strong indicator of the result, and when selecting between PD and HD for ESRD ailments, it is a key factor to consider ( 23 , 24 , 37 , 38 ). It seems that psychological variables can determine the way an individual interacts with himself and his life, and this determines level of control over life, which also affects dialysis adequacy and laboratory indicators ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, frequent occurrences of loud beeping sounds in APD machines, which are necessary to alert PD patients of machine problems, may lead to sleep disorders or even burnout and frustration in PD patients (Mizuno et al, 2016). However, PD patients can seek diverse supports to alleviate such disturbances and negative emotions, which can enable patients to adapt to PD more quickly.…”
Section: Discussionmentioning
confidence: 99%